Dynamic surface tension of xylem sap lipids - Yang, Jinlong; M Michaud, Joseph; Jansen, Steven; Schenk, H Jochen; Zuo, Yi Y (Tree physiology, 2020)
Abstract The surface tension of xylem sap has been traditionally assumed to be close to that of the pure water because decreasing surface tension is thought to increase vulnerability to air seeding and embolism. However, xylem sap contains insoluble lipid-based surfactants, which also coat vessel and pit membrane surfaces, where gas bubbles can enter xylem under negative pressure in the process known as air seeding. Because of the insolubility of amphiphilic lipids, the surface tension influencing air seeding in pit pores is not the equilibrium surface tension of extracted bulk sap but the local surface tension at gas–liquid interfaces, which depends dynamically on the local concentration of lipids per surface area. To estimate the dynamic surface tension in lipid layers that line surfaces in the xylem apoplast, we studied the time-dependent and surface area-regulated surface tensions of apoplastic lipids extracted from xylem sap of four woody angiosperm plants using constrained drop surfactometry. Xylem lipids were found to demonstrate potent surface activity, with surface tensions reaching an equilibrium at ~25 mN m-1 and varying between a minimum of 19 mN m-1 and a maximum of 68 mN m-1 when changing the surface area between 50 and 160% around the equilibrium surface area. It is concluded that xylem lipid films in natural conditions most likely range from nonequilibrium metastable conditions of a supersaturated compression state to an undersaturated expansion state, depending on the local surface areas of gas–liquid interfaces. Together with findings that maximum pore constrictions in angiosperm pit membranes are much smaller than previously assumed, low dynamic surface tension in xylem turns out to be entirely compatible with the cohesion–tension and air-seeding theories, as well as with the existence of lipid-coated nanobubbles in xylem sap, and with the range of vulnerabilities to embolism observed in plants.